379. A budget impact analysis of bezlotoxumab for the management of recurrent Clostridioides difficile infection in the United States. (15th December 2022) - Jiang, Yiling; Deshpande, Abhishek; Li, Qinghua; Siegartel, Lisa; Siddiqui, Fakhar; Obi, Engels N
Abstract: Background: Clostridioides difficile infection (CDI) is one of the most frequently reported healthcare-associated infections in the US with almost half a million cases reported annually. The most recent IDSA guidelines recommend use of bezlotoxumab (BEZ) in addition to standard of care (SoC) antibiotics for patients who have a CDI episode and at least one risk factor for recurrence. The objective of this study was to estimate the budget impact of the use of BEZ+SoC vs SoC alone from a hospital perspective in the US. Methods: A decision analytic model was developed, considering treatment of the index recurrent CDI (rCDI) episode and subsequent recurrences (a maximum of two) over a one-year period, in patients who had at least one risk factor of rCDI. Two scenarios were compared: one with BEZ+SoC, and one with SoC alone. The analysis included costs and payments of medications and the cost of managing rCDI, as well as proportion of BEZ utilization across management settings (with the assumption of 50% inpatient and 50% outpatient). Parameters were retrieved from published sources and expert opinion was sought. The budget impact was calculated as the difference in revenue (difference in payments and costs) between scenarios. One-way sensitivity analyses were performed on key parameters. Costs were expressed in 2021/2 US dollars. Results: Among 10, 000 hypothetical hospitalizations, treatment with BEZ+SoC of at-risk patients instead of SoC alone in the base case analysis was estimated to result in a potential savings of $53, 361 at the hospital level, $497 per treated rCDI patient, and $5.34 per admitted patient. The additional cost of BEZ was offset by the lower rCDI rate in those treated with BEZ. Sensitivity analyses demonstrated the robustness of results. Conclusion: For patients with CDI and at risk for recurrence, treatment with BEZ+SoC is cost saving from a hospital perspective. Broader benefits of BEZ+SoC should be considered by healthcare stakeholders and policy makers when making decisions about formulary inclusion and adoption. Disclosures: Yiling Jiang, MSc, MSD (UK) Ltd.: Employment|MSD (UK) Ltd.: Stocks/Bonds Abhishek Deshpande, MD, PhD, Clorox: Grant/Research Support|Merck: Advisor/Consultant|Seres Therapeutics: Grant/Research Support Qinghua Li, PhD, Merck & Co., Inc.: employee Lisa Siegartel, MPH, Merck & Co., Inc.: Employee|Merck & Co., Inc.: Ownership Interest Fakhar Siddiqui, MD, MBA, Merck & Co., Inc.: employee|Merck & Co., Inc.: Stocks/Bonds Engels N. Obi, PhD, Merck & Co., Inc.: Employee|Merck & Co., Inc.: Stocks/Bonds.